An Investigation on Differences in the Earnings through Alternative Marketing Channels: A Study on Rice Farmers in Jessore District of Bangladesh - Rahman, Shaikh Moksadur (Indian Journal of Marketing, 2006)
Due to the limits on alternative ways of improving the living conditions of the farmers, and as rice is one of the main sources of income for rural farmers, its efficient alternative marketing channel is considered as an important instrument in contributing more money for them, and that will lead to a better standard of living. This study focuses on the standard of living, production structure or rice, marketing channel, rice selling, prices, marketing cost and net earnings, earnings differences and farmers' attitudes towards marketing. A field survey was conducted using the interview method during July to August 2003, in one village (Azampur) of Jhikargacha Upazila in Jessore district of Bangladesh. In the study, 33 rice farmers were randomly selected as respondents where farmers used six types of marketing channels for selling unpolished and polished rice. The study compared on the differences in the earnings through alternative channels and found that the farmers could earn more money when they used the channel for selling the polished rice to the retailers of the polished rice than all other channels. The study also found that a very small amount of rice was sold through the efficient alternative channels due to poor socio economic conditions and marketing problem.